Mir-106b-5p: a master regulator of potential biomarkers for breast cancer aggressiveness and prognosis - Farré, Paula Lucía (2021)
Breast cancer (BCa) is the leading cause of death by cancer in women worldwide. This disease is mainly stratified in four subtypes according to the presence of specific receptors, which is important for BCa aggressiveness, progression and prognosis. MicroRNAs (miRNAs) are small non-coding RNAs that have the capability to modulate several genes. Our aim was to identify a miRNA signature deregulated in preclinical and clinical BCa models for potential biomarker discovery that would be useful for BCa diagnosis and/or prognosis. We identified hsa-miR-21-5p and miR-106b-5p as up-regulated and hsa-miR-205-5p and miR-143-3p as down-regulated in BCa compared to normal breast or normal adjacent (NAT) tissues. We established 51 shared target genes between hsa-miR-21-5p and miR-106b-5p, which negatively correlated with the miRNA expression. Furthermore, we assessed the pathways in which these genes were involved and selected 12 that were associated with cancer and metabolism. Additionally, GAB1, GNG12, HBP1, MEF2A, PAFAH1B1, PPP1R3B, RPS6KA3 and SESN1 were downregulated in BCa compared to NAT. Interestingly, hsa-miR-106b-5p was up-regulated, while GAB1, GNG12, HBP1 and SESN1 were downregulated in aggressive subtypes. Finally, patients with high levels of hsa-miR-106b-5 and low levels of the abovementioned genes had worse relapse free survival and worse overall survival, except for GAB1.